Comparison of Pharmacy Claims and Electronic Pill Bottles for Measurement of Medication Adherence Among Myocardial Infarction Patients. Issue 2 (February 2019) - Mehta, Shivan J.; Asch, David A.; Troxel, Andrea B.; Lim, Raymond; Lewey, Jennifer; Wang, Wenli; Zhu, Jingsan; Norton, Laurie; Marcus, Noora; Volpp, Kevin G.
Abstract : Background: Medication adherence after myocardial infarction remains low. Pharmacy claims have typically been used to measure medication adherence, but electronic pill bottles may offer additional information. Objective: The main objectives of this study were to compare the association of adherence measured by prescription claims and remote monitoring technologies with cardiovascular events. Research Design: This study was a secondary analysis of a remote monitoring intervention to increase medication adherence in myocardial infarction patients. Subjects: In total, 682 myocardial infarction patients were randomized to the intervention group with both medical and pharmacy benefits. Measures: Pharmacy claims adherence was measured using proportion of days covered (PDC) and GlowCap adherence (GC) was measured as the proportion of days the pill bottle was opened. We compared the association of PDC and GC adherence for statins with time to first vascular readmission or death and assessed model fit using Akaike information criterion and Bayesian information criterion and the likelihood ratio test. Results: Higher PDC was significantly associated with a lower hazard rate for vascular readmissions or death (hazard ratio=0.435; P =0.009). There was also an association between GC adherence and vascular readmissions or death (hazard ratio=0.313; P ⩽0.001). Adding the GC adherence variable to the model using only PDC improved the model fit (likelihood ratio test, P =0.001), as well as vice versa ( P =0.050). Conclusions: Pharmacy claims data provide useful but not complete data for medication adherence monitoring. New wireless technologies have the potential to provide additional data about clinical outcomes. Abstract : Supplemental Digital Content is available in the text.